PENINGKATAN KOMPETENSI WISATA KEARIFAN LOKAL DALAM MENDUKUNG PENGEMBANGAN WILAYAH KELURAHAN TANJUNG PIAYU KECAMATAN SEI BEDUK - Andhika Pradita F; Syafrijal; Yuanita FD Sidabutar (Universitas Batam, 2023)
This research was conducted with the aim of increasing the competence of local wisdom tourism and supporting regional development in Tanjung Piayu Village, Sei Beduk District. Participatory methods are used to involve local residents and tourism actors in decision making and program implementation. Community participation in tourism development is increasing and contributions to economic and environmental sustainability in the region are increasingly visible. The research results show that increasing community participation in tourism development can make a significant contribution to economic and environmental sustainability in the region. The SWOT analysis method used in this research helps involve local residents and tourism actors in decision making and program implementation more effectively. In the training programs and workshops held, it can be seen that the knowledge and skills of local residents in managing local wisdom tourism are increasing. Increasing the competence of local wisdom tourism can play an important role in regional development. Training and outreach programs have also proven effective in increasing community participation in tourism development.